Thickness and surface profiling of optically transparent and reflecting samples using lens-less self-referencing digital holographic microscopy - Subhash Utadiya; Vismay Trivedi; Kevin Bhanderi; Mugdha Joglekar; Chaitanya Limberkar; Kireet Patel; Gyanendra Sheoran; Humberto Cabrera; Bahram Javidi; Arun Anand (Applied Surface Science Advances, 2023)
Thickness and surface profiling of transparent/semi-transparent specimens are vital in various applications, including electronics, optics, healthcare, and biotechnology. Surface profiling techniques characterize and analyze surface thickness, morphology, and roughness. Developing easy-to-use, single-shot, wide field-of-view techniques that provide nanometer level surface thickness and profiling is vital for these applications. Digital holography is a state-of-the-art technique that provides the quantitative phase images of transparent objects, from which their thickness profiles could be extracted and used for surface profiling. It has the added advantage of numerical focusing. The present manuscript details the development of a compact wide field of view, self-referencing, lens-less digital holographic microscope for surface profiling of transparent/semi-transparent samples in transmission and reflection mode. The developed microscope requires only a glass plate to generate holograms and can be used to study the dynamics of the surfaces also. It provides a field of view of 3.2mm x 2.5 mm along with a thickness measurement resolution of 2.8 nm and temporal stability of 1.1 nm over a period of 120 s. The developed microscope was tested by measuring the thickness of GeSe semiconductor thin films grown on glass substrates and comparing it with AFM measurements. The microscope was then used to quantify spatially varying thickness profiles of overlapped thin films, junction formed by heterogenous compounds and metal thin films. The microscope was also tested for dynamic studies of surface profiles by thermally loading ink markings on glass slides.